The Hubungan Rasionalitas Penggunaan Antibiotik Terhadap Keberhasilan Terapi Pada Pasien Anak Terdiagnosis Pneumonia di Instalasi Rawat Inap RSUD dr. R. Soedjati Purwodadi Menggunakan Metode Gyssens - Anggi Fajriatu Hidaya; Tista Ayu Fortuna (Journal of Pharmaceutical and Sciences, 2025)
Pneumonia is an inflammation of the lung parenchyma that can be caused by microorganisms including fungi, viruses, bacteria, and mycobacteria. In addition, chronic inflammatory diseases of the respiratory tract can be characterized by wheezing, chest tightness, and coughing accompanied by flu. To evaluate the rational use of antibiotics, the Gyssens method was developed, which includes the appropriate selection of antibiotics based on effectiveness, toxicity, lower cost, narrower spectrum, duration of administration, dose, interval, route, and timing of administration. A patient's improvement or lack thereof can be assessed based on body temperature, white blood cell count, respiratory rate, and clinical symptoms. The study design is non-experimental (observational) with a cross-sectional study design. Data collection was conducted retrospectively using data from medical records of pediatric patients diagnosed with pneumonia at Dr. R. Soedjati Purwodadi General Hospital, with a total of 110 pediatric patients meeting the inclusion criteria. The results showed that 38 patients (34.55%) received antibiotics irrationally, with the most inaccuracies in the drug selection category (IV A, IV C, and IV D). A total of 72 users (65.45%) were rational and 38 users (34.55%) were irrational. The results of statistical analysis of the data using the Chi-Square test show that these results were obtained from the Exact Sig (2-sided) value, namely p = 0.003 (p < 0.05), so it can be interpreted that there is a rational relationship between the use of antibiotics and the success of therapy in pediatric patients.